Land-to-sea indicators of the Zanclean megaflood - Aaron Micallef; Giovanni Barreca; Christian Hübscher; Angelo Camerlenghi; Paul Carling; Jose Maria Abril Hernandez; Raúl Periáñez; Daniel Garcia-Castellanos; Jonathan Ford; Benedikt Haimerl; Matthias Hartge; Jonas Preine; et al. (Communications Earth & Environment)
Abstract One debated scenario for the termination of the Messinian salinity crisis 5.33 million years ago is cataclysmic refilling of the Mediterranean Sea through the Zanclean megaflood. Here we present a clear line of onshore-to-offshore evidence for this megaflood spilling over a shallow-water marine corridor in south-east Sicily into the nearby subaqueous Noto Canyon: (i) >300 asymmetric and streamlined erosional ridges aligned with the megaflood direction, (ii) poorly-sorted breccia deposited between the Messinian and Lower Zanclean Trubi Formations, (iii) soft-sediment deformation structures and clastic injections in the breccia and underlying units, and (iv) a 20 kilometre wide erosional shelf channel connecting the ridges with Noto Canyon. Numerical modelling results support the modulation of flow velocity and direction by the excavation of the channel and Noto Canyon. Our findings demonstrate that the Messinian salinity crisis was terminated through a cataclysmic flood, which implies pronounced Mediterranean sea-level drawdown prior to the flooding.